Estudo numérico de um dispositivo de coluna de água oscilante para aproveitamento da energia das ondas do mar - Thums, Esmael (Universidade do Vale do Rio dos Sinos, 2023)
Energy conversion devices from waves harness the kinetic energy of seawater movement and convert it into electrical energy. Oscillating water column (OWC) devices use the motion of the sea surface to compress the air in a hydro-pneumatic chamber connected to a duct containing a turbine, which, in turn, drives a generator. Considering that existing wave energy converters have low efficiency, the literature suggests that there is room for improvement in this type of device. The Constructal Design Method (CDM) has been used to search for designs that can maximize the available energy. Through numerical modeling and the use of computational fluid dynamics (CFD), researchers have studied how the geometry of converters affects their performance and how it can be optimized. In this study, CDM is employed with the assistance of Design of Experiments (DoE) techniques and optimization to obtain the optimal design for a two-chamber OWC device based on the results of CFD simulations. The considered system is a full-scale device subjected to waves with a length of 65.4 m, a period of 7.5 s, and a height of 1 m. The volume ratios between the two chambers and the aspect ratios of each chamber (V1/V2, H1/L1, and H2/L2) are the three degrees of freedom used for optimizing the performance indicator, which is the power extracted per wave cycle. By generating a response surface, it was possible to observe that the bestperforming device had V1/V2 = 1.2, H1/L1 = 0.34, and H2/L2 = 0.1, resulting in a mass flow rate of 34.41 kg/s, a pressure of 2643.031 Pa, and a hydropneumatic power of 8875.15 W.
Keywords: Energia das ondas do mar; Coluna de água oscilante; Energias renováveis; Ocean wave energy; Oscillating water column; Renewable energies; ACCNPQ::Engenharias::Engenharia Mecânica